Blood–brain barrier breakdown, central nervous system cell damage, and infiltrated T cells as major adverse effects in CAR-T-related deaths: a literature review - Del Duca, Fabio; Napoletano, Gabriele; Volonnino, Gianpietro; Maiese, Aniello; La Russa, Raffaele; Di Paolo, Marco; De Matteis, Serena; Frati, Paola; Bonafè, Massimiliano; Fineschi, Vittorio (Frontiers in Medicine, 2024)
Background: CAR-T-related deaths observed worldwide are rare. The underlying pathogenetic mechanisms are the subject of study, as are the findings that enable diagnosis. A systematic literature search of the PubMed database and a critical review of the collected studies were conducted from the inception of this database to January 2023. The aim of the study is to determine when a death is related to CAR-T cell therapy and to develop a shareable diagnostic algorithm.The database was searched by combining and meshing the terms ("CAR-t" OR "CART") AND ("Pathology" OR "Histology" OR "Histological" OR "Autopsy") AND ("Heart" OR "Cardiac" OR "Nervous System" OR "Kidney" OR "Liver") with 34 results and also the terms: ((Lethal effect) OR (Death)) AND (Car-t therapy) with 52 results in titles, abstracts, and keywords [all fields]. 100 scientific articles were examined, 14 of which were additional records identified through other sources. Fifteen records were included in the review.Results: Neuronal death, neuronal edema, perivascular edema, perivascular and intraparenchymal hemorrhagic extravasation, as well as perivascular plasmatodendrosis, have been observed in cases This is a provisional file, not the final typeset article with fatal cerebral edema. A cross-reactivity of CAR-T cells in cases of fatal encephalopathy can be hypothesized when, in addition to the increased vascular permeability, there is also a perivascular lymphocyte infiltrate, which appears to be a common factor among most authors.Most CAR-T-related deaths present with blood-brain barrier breakdown and central nervous system cell damage and infiltrated T-cells. Further autopsies and microscopic investigations would shed more light on the lethal toxicity related to CAR-T cells. Diffential diagnosis of CAR-T related death is crucial to identify adverse events. In this paper, we proposed an algorithm, that could facilitate the comparison of findings through a systematic approach. Despite toxicity cases, CAR-T therapy continues to stand out as the most innovative treatment within the field of oncology, and emerging strategies hold the promise of delivering safer therapies in the future.